The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/anie.201900983
|View full text |Cite
|
Sign up to set email alerts
|

First Synthesis and Characterization of CH4@C60

Abstract: The endohedral fullerene CH 4 @C 60 , in which each C 60 fullerene cage encapsulates a single methane molecule, has been synthesized for the first time. Methane is the first organic molecule, as well as the largest, to have been encapsulated in C 60 to date. The key orifice contraction step, a photochemical desulfinylation of an open fullerene, was completed, even though it is inhibited by the endohedral molecule. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 59 publications
6
65
0
Order By: Relevance
“…Allowing for the nonrigidity of the lattice, not considered in the Devonshire cell model, introduces two effects changing the quantum treatment of these systems: (a) the host–guest (molecule–crystal) interaction energy is minimized by the relaxation of the lattice, and (b) the orientation‐dependent lattice relaxations, through coupling of the guest rotations with pseudorotation of the host, induce a significant change, in fact a decrease of the effective rotational constants. Recently, quantum studies of molecules trapped in cages found renewed interest, especially with regard to the joint treatment of translation–rotation states. Answering the question whether these systems are quasistructural or not would require detailed experimental high‐resolution spectroscopic studies and variational rovibrational treatments, both hindered by the size of some of these systems.…”
Section: On the Separation Of Vibrations And Rotationsmentioning
confidence: 99%
“…Allowing for the nonrigidity of the lattice, not considered in the Devonshire cell model, introduces two effects changing the quantum treatment of these systems: (a) the host–guest (molecule–crystal) interaction energy is minimized by the relaxation of the lattice, and (b) the orientation‐dependent lattice relaxations, through coupling of the guest rotations with pseudorotation of the host, induce a significant change, in fact a decrease of the effective rotational constants. Recently, quantum studies of molecules trapped in cages found renewed interest, especially with regard to the joint treatment of translation–rotation states. Answering the question whether these systems are quasistructural or not would require detailed experimental high‐resolution spectroscopic studies and variational rovibrational treatments, both hindered by the size of some of these systems.…”
Section: On the Separation Of Vibrations And Rotationsmentioning
confidence: 99%
“…Encapsulation of Li + ion inside the C 60 cage was done experimentally by Hiroshi et al 47 Experimentally it is reported that La atom can be inserted into the cavity of C 72 , C 74 , C 82 cages 48–50 . Encapsulation of H 2, 51,52 H 2 O, 53 HF, 54 CH 4 55 molecules inside fullerene were done using the “molecular surgery” technique. Various theoretical works on the encapsulation of different metals and noble gases inside the C 60 cage have been reported 56–59 .…”
Section: Introductionmentioning
confidence: 99%
“…Upon irradiation of Ar@4 for 35 h under these conditions, at 50 1C using a low-pressure sodium lamp, the bis(hemiketal) Ar@5 was obtained in 26% yield of isolated product. Our previously reported photochemical desulfinylation of CH 4 @4 led to the corresponding bis(hemiketal) CH 4 @5 in only 13% yield under the same conditions, 19 indicating that contraction of the cage-opening is less inhibited by argon, the smaller endohedral species.…”
mentioning
confidence: 85%
“…by closure of the orifice of CH 4 @3 to obtain CH 4 @C 60 . 19 Herein, we report that high encapsulation of argon by 3 can be achieved under similar conditions, and closure allows synthesis of Ar@C 60 with a step-change improvement in argon incorporation, mass recovery and yield when compared to the direct encapsulation method.…”
mentioning
confidence: 94%
See 1 more Smart Citation